Динаміка змін генерації сили та довжини м'язових волокон під впливом рутину - Ноздренко, Д.М.; Прилуцький, Ю.І. (Видавничий дім "Академперіодика" НАН України, 2007)
The changes of dynamic parameters of the contraction of skeletal muscle fibers of m. tibialis Rana temporaria frog in the isotonic condition during the modulated stimulation under the rutin solution action in the concentration range (10–5–10–3) mol/l are studied in detail.